CRYSTAL STRUCTURE REFINEMENTS OF PALYGORSKITE AND MAYA BLUE FROM MOLECULAR MODELLING AND POWDER SYNCHROTRON DIFFRACTION - Chiari G.; Giustetto R.; Ricchiardi G. (My University, 2003)
Maya Blue, a synthetic pigment produced by the ancient Mayas, is a combination of a specific clay, palygorskite (or sepiolite), containing large channels in the crystal structure and the organic dye indigo. Little is known about the interaction of the two components to give the most stable pigment ever produced. The aim of this work is to obtain a refined model for the Mexican palygorskite used to prepare the pigment and to elucidate the structure of the clay-indigo complex, using both molecular modelling and Rietveld refinement on data collected with synchrotron radiation. Molecular modelling proved that indigo can fit into the channels without steric impediment (forming strong hydrogen bonds between the C=O group of the dye and the structural water of the clay) and produced a model, showing reasonable distances and angles, used as the starting set for the Rietveld refinement. Difference Fourier maps, calculated without indigo, showed a residual of electron density coherent with the expected disordered position of the indigo molecule. A refinement carried out using the model of palygorskite obtained in this work and a 6-fold disordered arrangement of indigo confirmed these findings. The ratio between the two polymorphs of palygorskite (monoclinic and orthorhombic) present in the natural clay was obtained for our sample and for several palygorskite specimens coming from different sites. Samples within the same outcrop show similar ratios, while samples from different locations do not. This may be used to characterize the provenance of ancient specimens, with the goal of determining whether Maya Blue was invented and produced in one place only or if the production technology was widespread in all the Mayan region.
Keywords: Palygorskite